PENGEMBANGAN e-LKPD BERBASIS PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI ASAM BASA - Shinta Nissa Mutia; M. Naswir; Isra Miharti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to determine the process of developing e-LKPD based on Project Based Learning (PjBL) to improve students' critical thinking skills on acid-base materials, as well as to determine the feasibility and student response to the developed e-LKPD. This research uses the Lee & Owens development model. The research instruments used were interview guidelines and questionnaires. The developed product was validated by media experts and content experts, evaluated by chemistry teachers, and subsequently tested on a small group. The data analysis techniques used are qualitative data analysis and quantitative data analysis. Based on the results of media expert validation, the average score obtained was 4.53 with a "Very Feasible" category. The results of material expert validation yielded an average score of 4.26 with a "Very Feasible" category. Based on teacher assessment, the average score was 4.73 with a "Very Feasible" category. And student responses in the small group test yielded a percentage of 90.26% with a "Very Good" category. Based on the development and research results, it can be concluded that the e-LKPD teaching material based on Project Based Learning (PjBL) to improve students' critical thinking skills on acid-base material is considered highly suitable for use in chemistry learning.